Differentiation-inducing ability of sophorolipids of oleic and linoleic acids using a glioma cell line - Joshi-Navare, Kasturi; Shiras, Anjali; Prabhune, Asmita (Biotechnology Journal, 2011)
Sophorolipids are biosurfactants produced by non-pathogenic yeasts. They show structural similarity with the membrane components of mammalian cells, i.e., glycosphingolipids and gangliosides, which are involved in processes such as signaling, oncogenesis, and differentiation. Sophorolipids have been reported to induce differentiation in several leukemic cell lines, cell death via apoptosis in a human liver cancer cell line, and necrosis in a pancreatic adenocarcinoma cell line. Here we report, for the first time, the effects of precursor fatty acids and sophorolipids of oleic and linoleic acids in pure acidic and crude forms on LN-229, a glioma cell line. In response to different sophorolipid forms, various morphological changes were observed, such as formation of long thread-like extensions arising from the ends of the cells, cell alignment, cell elongation and bundle formation in a dose-dependent manner. In this study we present the morphological evidence of the potential of sophorolipids as differentiation inducers.
Keywords: Differentiation; Glioma; LN-229; Sophorolipid